Pelatihan Media Presentasi Powtoon dan Sparcol Untuk Guru SD Negeri 9 Purwodadi, Grobogan - Fathoni, Achmad; Rosyadi, Ajib; Gunawan, Indra; Hidayat, Muhammad Taufik; Puspasari, Afrin (Prosiding University Research Colloquium, 2019)
The purpose of this social service is to provide learning media training based on the presentation application, Sparcol and Powtoon. This activity was given to teachers in Elementary School 9 Purwodadi. The social service session consists of installing an application, creating an account, adding images and text, changing the background, and saving the results that have been made. The model used is a workshop model with lectures, demonstrations, question and answer and direct practice methods. Evaluation is done by distributing information and motivation questionnaires to participants and product checklists. In general, participants claimed that the training schedule was right, the time sharing (lectures, demonstrations, question-answer and direct practice) was also felt positively by the participants. Participants are satisfied with the topic presented and feel that most of the expectations and objectives of the social service are fulfilled. Evaluation results indicate that the material delivered can be followed well.